Investigating Speaking Skills Acquisition Through the Audio-Oral Method in Higher Education: A Case Study of the Department of Arabic, The New College, Chennai, India - Dr K M A AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This research aims to investigate the teaching of speaking skills using the audio-oral method among students at the Department of Arabic, The New College, Chennai as well as to identify the challenges faced in this approach. Employing a qualitative methodology, data was gathered through observations, interviews, and documentation. Data analysis was structured around three key components: data reduction, data presentation, and extrapolation. To ensure data validity, triangulation was utilized. The findings indicate that speaking skills are taught using the audio-oral method by providing dialogues that are subsequently translated and modeled in the Arabic dialect. Students listen to these pronunciations and practice imitating them; at times, a mobile phone recorder is employed to enhance their proficiency in speaking Arabic accurately. The teaching process is complemented by additional exercises involving diverse Arabic dialogues. The challenges encountered in teaching speaking skills using the audio-oral method at this institution are primarily related to the language environment, the influence of the local language, and issues stemming from a monotonous teaching approach and inadequate learning materials.